The Main Geohazards in the Russian Sector of the Arctic Ocean - Artem A. Krylov; Daria D. Rukavishnikova; Mikhail A. Novikov; Boris V. Baranov; Igor P. Medvedev; Sergey A. Kovachev; Leopold I. Lobkovsky; Igor P. Semiletov (Journal of Marine Science and Engineering)
The Arctic region, including vast shelf zones, has enormous resource and transport potential and is currently key to Russia’s strategic development. This region is promising and attractive for the intensification of global economic activity. When developing this region, it is very important to avoid emergency situations that could result in numerous negative environmental and socio-economic consequences. Therefore, when designing and constructing critical infrastructure facilities in the Arctic, it is necessary to conduct high-quality studies of potential geohazards. This paper reviews and summarizes the scattered information on the main geohazards in the Russian sector of the Arctic Ocean, such as earthquakes, underwater landslides, tsunamis, and focused fluid discharges (gas seeps), and discusses patterns of their spatial distribution and possible relationships with the geodynamic setting of the Arctic region. The study revealed that the main patterns of the mutual distribution of the main geohazards of the Russian sector of the Arctic seas are determined by both the modern geodynamic situation in the region and the history of the geodynamic evolution of the Arctic, namely the formation of the spreading axis and deep-sea basins of the Arctic Ocean. The high probability of the influence of seismotectonic activity on the state of subsea permafrost and massive methane release is emphasized. This review contributes toward better understanding and progress in the zoning of seismic and other geological hazards in the vast Arctic seas of Russia.